A Navigational Evaluation Model for Content Management Systems - Gilani, S.; Majeed, A.; Muzammal, M.; Rehman, A. U.; Zaheer, H.; Jan, Z. (The Nucleus, 2017)
Web applications are widely used world-wide, however it is important that the navigation of these websites is effective, to enhance usability. Navigation is not limited to links between pages, it is also how we complete a task. Navigational structure presented as hypertext is one of the most important component of the Web application besides content and presentation. The main objective of this paper is to explore the navigational structure of various open source Content Management Systems from the developer’s perspective. For this purpose three CMS are chosen which are WordPress, Joomla, and Drupal. Objective of the research is to identify the important navigational aspects present in these CMSs. Moreover, a comparative study of these CMSs in terms of navigational support is required. For this purpose an industrial survey is conducted based on our proposed navigational evaluation model. The results shows that there exist correlation between the identified factors and these CMSs provide helpful and effective navigational support to their users.